Entre le « vous » et le « je » cet objet macabre: Intervention poétique-érotique dans « Une Charogne » - Calhoun, Doyle (Lingua Frankly, 2016)
This paper provides a reading attentive to linguistic features of Baudelaire's poem "Une Charogne."